Study of using three dimensional printer for EDM electrode fabrication - Hassan, Noor Haslyena (2011)
In this study, Cu-Al2O3 powder was prepared using ball mill and used separately for powder metallurgy (PM) and Three Dimensional Printer (3DP) application to fabricate electrode for electrical discharge machining (EDM). The materials in powder form were analyzed under scanning electron microscope (SEM) and particle size analyzer (PSA) to ensure that they fulfill the requirement for each fabrication method. For PM process, five compositions of Cu-%wt Al2O3 powder were prepared ranging from 0% to 20% Al2O3 contents at 5% increment. The powder were compacted and sintered in argon protected atmosphere to determine the suitable compaction pressure and sintering temperature to fabricate PM electrode. Microscopic analysis revealed that 48MPa and 921°C is the best compaction pressure and sintering temperature respectively for EDM electrode fabrication. EDM electrode samples were fabricated using both recommended parameters, and were tested to erode JIS SKD11 (mould steel) workpiece for 5 minutes, with solid Cu electrode as the benchmark. Electrodes’ performances were assessed by calculating the tool wear rate (TWR), material removal rate (MRR) and by measuring the average surface roughness (Ra) of the eroded cavity. From the experiment conducted, the PM electrodes are not as good as solid Cu electrode in terms of MRR, but the addition of Al2O3 at around 10%wt could reduce the TWR and Ra. The composition of Cu-10%wt Al2O3 powder electrode that has the optimum machining results was then prepared for 3DP application. Green parts were fabricated using 3DP, sintered and infiltrated prior to being tested at EDM machine. Although sintering was a success, samples were still porous due to the failure in infiltration process. The performance of EDM electrodes fabricated using 3DP were evaluated the same way as the ones fabricated via PM process. Experiments using 3DP electrodes showed that the electrodes depleted and became the alloying element on the workpiece. Further studies are needed on the sintering and infiltration method in order to improve the quality of the electrode fabricated using 3DP.